MENANAMKAN NILAI GOTONG ROYONG SEJAK DINI: STUDI KASUS DI SDN 101765 BANDAR SETIA - Rizky Wahida Arni Malau; Yakobus Ndona; Daulat Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the process of instilling the value of mutual cooperation in students of SDN 101765 Bandar Setia, considering that the spirit of togetherness among elementary school children currently tends to weaken due to the influence of technological developments, especially the use of gadgets. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation, involving the principal, teachers, students, and supporting documents from the school. The results of the study revealed that the habituation method is the main step in building the character of mutual cooperation through various activities, such as class duty, group work, community service activities, and clean Friday. Therefore, the implementation of habituation needs to be continuously improved so that students are accustomed to having an attitude of mutual help and responsibility, with full support from all related parties.